Business management: Case study applied to Brazilian army information systems - Santos, Rômulo Ferreira dos; Silva, Rodrigo Florêncio da; Silva, Adriana Farias da (Seven Editora, 2024)
This article examines the integration between Business Management and Information Systems within the Brazilian Army, highlighting how this confluence supports strategic and operational objectives in a military context. Focusing on the effective structuring of data and information with a view to facilitating usability and accessibility, the study investigates the management of resources and the application of information systems with a view to optimizing organizational performance and continuous improvement. Using a methodology consisting of document analysis, bibliographical research and field studies, including interviews and direct observations, the aim is to evaluate the efficiency of current practices and identify possible gaps and challenges faced by the institution. The relevance of this study is underlined by the need for business management approaches that are innovative, sustainable and socially responsible, especially considering the specific demands of security, secrecy and operational effectiveness inherent to military institutions. In addition, the article proposes an Information Architecture for strategic information management where the benefits of business management are discussed based on the GPD and PDCA methodologies that promote a systematic and objective-oriented approach that is fundamental to achieving consistent results in line with the Brazilian Army's strategic guidelines. DOI:https://doi.org/10.56238/sevened2024.010-026